Odpowiedzi

Najlepsza Odpowiedź!
2009-12-04T20:06:48+01:00
2x+3y=0,5
3x+y=-1

przeciwnych

2x+3y=0,5
3x+y=-1 /*-3

2x+3y=0,5
-9x-3y=3
-7x=3,5
x=-0,5

2*-0,5+3y=0,5
-1+3y=0,5
3y=1,5
y=0,5

podstawiania
2x+3y=0,5
3x+y=-1

y=-1-3x

2x+3(-1-3x)=0,5
2x-3-9x=0,5
-7x=3,5
x=-0,5

y=-1-3*-0,5
y=-1+1,5
y=0,5

to niżej jest źle ma wyjść x=-0,5
  • Herx
  • Rozwiązujący
2009-12-04T20:08:44+01:00
{2x+3y=0.5|*3 >>> {6x+9y=1.5
{3x+y=-1 |*(-2) >>> {-6x-2y=2

7y=3.5 |:7
y=0.5

2x+3*0.5=0.5
2x+1.5=0.5
2x=1|:2
x=0.5